Redescription of the subgenus Parancistrum Verhoeff, 1943, an eastern Mediterranean lineage of the millipede genus Megaphyllum Verhoeff, 1894 (Diplopoda: Julida: Julidae: Brachyiulini) - Vagalinski, Boyan; Lazányi, Eszter; Golovatch, Sergei (Zootaxa, 2013)
The subgenus Parancistrum Verhoeff, 1943 is redefined on the basis of the examination of type and non-type material. The subgenus is currently settled to comprise 6 species, of which Megaphyllum arcuatum sp. n. is described as new, while M. adanense (Verhoeff, 1943) syn. n. and M. palaestinum (Jawłowski, 1931) syn. n. are established as junior subjective synonyms of M. curvifolii (Verhoeff, 1898) and M. genezarethanum (Verhoeff, 1923) comb. nov., respectively. A neotype is designed for Chromatoiulus tenenbaumi Jawłowski, 1931 under ICZN Article 75.1. The distribution pattern of the studied group is discussed, and some preliminary phylogenetic ideas about Megaphyllum and the tribe Brachyiulini are presented.